FAKTOR - FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Elisa, Elisa; Sumarta, Rian (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research aims to obtain empirical evidence regarding the influence of service quality, tax sanctions, tax knowledge, taxpayer awareness, tax socialization, financial conditions, and e-billing implementation on the compliance of individual taxpayers. The subjects of this study are individual taxpayers registered in the DKI Jakarta area. The sampling method employed in this research is purposive sampling, with a total of 91 respondents. The results of this study indicate that the variables of service quality, tax knowledge, taxpayer awareness, and tax socialization have an impact on the compliance of individual taxpayers. Meanwhile, tax sanctions, financial conditions, and e-billing implementation do not affect the level of compliance of individual taxpayers.